2017
DOI: 10.1002/dvdy.24524
|View full text |Cite
|
Sign up to set email alerts
|

A role for primary cilia in aortic valve development and disease

Abstract: Background Bicuspid aortic valve (BAV) disease is the most common congenital heart defect affecting 0.5–1.2% of the population and causes significant morbidity and mortality. Only a few genes have been identified in pedigrees and no single gene-model explains BAV inheritance, thus supporting a complex genetic network of interacting genes. However, patients with rare syndromic diseases that stem from alterations in the structure and function of primary cilia (“ciliopathies”) exhibit BAV as a frequent cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 62 publications
(78 reference statements)
3
62
0
Order By: Relevance
“…Valve endothelial cells and their human counterpart iPS cell-derived HPVCs expressing endocardial genes TBX2, TBX20, PITX2, GATA5, SMAD6 and MSX1 (Supplementary Fig. 4), expressed few cilia (data not shown) as recently reported in mouse 46 potentially because the high shear stress in the region of cardiac cushions as proposed in zebrafish 47 . EMT was thus induced by BMP2 treatment of HPVCs and cilia were scored in vimentin+ valvular interstitial cells (Fig.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Valve endothelial cells and their human counterpart iPS cell-derived HPVCs expressing endocardial genes TBX2, TBX20, PITX2, GATA5, SMAD6 and MSX1 (Supplementary Fig. 4), expressed few cilia (data not shown) as recently reported in mouse 46 potentially because the high shear stress in the region of cardiac cushions as proposed in zebrafish 47 . EMT was thus induced by BMP2 treatment of HPVCs and cilia were scored in vimentin+ valvular interstitial cells (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Primary ciliary dyskinesia (PCD) without sinus invertus as well as other ciliopathies have been clinically associated with myxomatous mitral valve and other valve diseases 71,46 Interestingly, patients with autosomal dominant polycystic kidney disease (ADPKD), a disease in which cells feature a over-activation of SHH pathway 72 have an increased occurrence of mitral valve prolapse 73 . Dachsous is required for lymphatic valve development 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis in non-ciliopathies has also been linked to the primary cilium. In investigating the mechanisms underlying fibrosis after cardiac injury, Toomer et al found that conditional knockout of IFT88 in adult mouse heart leads to increased expression of ECM components, including the proteoglycan versican, and formation of immature collagen fibres, indicating involvement of a post-transcriptional defect [39]. Also, Villalobos et al found evidence of a relationship between TGFβ-SMAD2/3 signalling, collagen expression and cilia in the context of cardiac fibrosis [40].…”
Section: Mechanical Forces Regulate Matrix Composition Through Ciliarmentioning
confidence: 99%
“…They possess sensory functions and serve as an important hub for signaling processes such as the Hedgehog (Hh) pathway (2). Activity of such signaling pathways is crucial during development (2) and is also needed for heart formation (3,4). Motile cilia, on the other hand, are typically found in multitudes, for instance on cells lining the surface of trachea, oviduct, and brain ventricles, and mainly serve to move fluids (1).…”
Section: Introductionmentioning
confidence: 99%